Effect of water-methanol binary solvent system in green synthesis of copper nanoparticles with tobacco leaf extract - Suharto, Tomi; Sudirman, Sudirman; Ulfa, Maria; Ningsih, Baiq Nila Sari; Putri, Khoiria Nur Atika; Thamsiri, Panthong (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
The increasing demand for environmentally friendly nanoparticle synthesis, as a viable strategy for pollution control, has prompted an exploration of green chemistry methods. This study meticulously investigates the synthesis of copper nanoparticles utilizing tobacco leaf extract obtained through both cold and hot extraction techniques. The primary focus lies in scrutinizing the impact of various solvents employed for plant extracts and metal ion solutions on reduction dynamics and particle size. The study employs UV-Vis and phytochemical analyses to discern differences in chemical composition and efficacy, particularly between the water and methanol-water systems, despite their resemblance in UV-Vis spectra. Intriguingly, the results unveil that the choice of solvent significantly influences the particle size distribution and stability of colloidal nanoparticles. The methanol-water system, in particular, yields smaller, more uniform particles compared to other solvent systems. This research sheds light on the pivotal role of solvent selection in nanoparticle synthesis, emphasizing its profound impact on both the reduction process and the resulting particle size distribution. The findings underscore the nuanced relationship between solvent choice and the characteristics of the synthesized nanoparticles, providing valuable insights for optimizing environmentally friendly synthesis methods. Ultimately, this study contributes to the growing body of knowledge on green chemistry approaches for nanoparticle synthesis with implications for pollution control and sustainable materials production.